Study on Prediction Model of Mechanical Parameters of Rock Frozen-Thawed Damage based on NMR Technology. (10th August 2022) - Tai, Yanzhi
Abstract : In order to establish prediction models for the mechanical parameters of rock freeze-thaw damage based on nuclear magnetic resonance (NMR) technology, with reference to the laboratory test of rock mechanical parameters after freeze-thaw, combined with low-field NMR and multivariate analysis methods, PLSR and PCR prediction models for the peak stress, peak strain, and elastic modulus of frozen-thawed rocks were established. The results show that the correlation coefficient of calibration set (R 2 cal ) and validation set (R 2 val ) of the PLSR and PCR prediction models are both greater than 0.9, and the residual prediction deviation (RPD) of each model is greater than 3, indicating that the established prediction models have good stability, small relative error, and high prediction accuracy. The application evaluation results show that the peak stress and peak strain of frozen-thawed rocks can be accurately predicted using these models. In this paper, only the NMR tests are performed on the frozen-thawed rocks, and no rock mechanics experiments are performed. The research results provide a new method for the research of rock freeze-thaw damage.